Influencia del conocimiento ambiental en las capacidades locales de la comunidad 12 de Octubre, sub-cuenca del río Carrizal - López Zambrano, José Javier (2017)
The research aimed to evaluate the influence of local capacities for the inhabitants of the Community environmental knowledge October 12, the Carrizal River Sub-basin, was not experimental, used participatory action research methodologies, applied to educational institutions. The quantitative method - was used for the identification of environmental knowledge deductive, interview techniques, tree problems, matrix Swot, training workshops with the method of learning by doing. For the determination of local capacities is based on the methodology of the programme for the development of the United Nations. According to the results, it was found that 86% of respondents if they received training in environmental education, and 14% have not had this opportunity; However, school teachers stated that they have environmental knowledge; This group has a science club within the institution as a means of learning; While parents do not have knowledge and they have not received training on this subject. In terms of local capacities, the researched group demonstrated abilities, skills, and techniques about the process of making compost and agro-ecological garden, same that respond to their needs of food security. Based on the findings, was prepared a proposal of good environmental practices of implementation of organic gardens.